DETERMINANTS OF THE HUMAN PAPILLOMAVIRUS (HPV) VACCINATION INTENTION AMONG STUDENTS - Milošević Gačević, Marijana; Petrović, Sandra (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Human papillomavirus (HPV) is the virus that is most often associated with cancers. Cervical cancer is one of the leading public health problems, especially in developing countries. In the Republic of Serbia, cervical cancer is the fifth most common cancer in the female population amongst all malignant diseases, and HPV infection is the most important risk factor for the occurrence of this disease. This study aims to identify the determinants of adolescent HPV vaccination intention. Materials and methods: The study was conducted as a cross-sectional study including a total of 748 students, aged 12 – 19 years, from one high school and two elementary schools in Šabac. The research instrument was a questionnaire, particularly constructed for this study. Multiple regression analysis was applied to examine the predictive model for explaining the HPV vaccination intention in young people. Results: The proposed model explains 66% of HPV vaccination intention in young people. The strongest predictor of HPV vaccination intention in young people relates to the subjective norm, i.e., social pressure from peers and other people who are important to them. Distrust of the benefit of vaccination, concern about commercial profiteering, and belief in a "vaccine conspiracy" have a significantly smaller but statistically significant contribution in explaining HPV vaccination intention amongst our youth. Conclusion: Increasing social pressure to get vaccinated, as well as changing certain attitudes and beliefs about vaccines in general, may lead to an increase in the intention of young people to get vaccinated against HPV. Understanding the key aspects of the attitudes of young people in Serbia towards HPV vaccination opens the possibility of creating evidence-based public health policies and planning targeted health-educational interventions directed at the identified findings.